2009
DOI: 10.1017/s0954579409000509
|View full text |Cite
|
Sign up to set email alerts
|

Resting heart rate and the development of antisocial behavior from age 9 to 14: Genetic and environmental influences

Abstract: The genetic and environmental basis of a well-replicated association between antisocial behavior (ASB) and resting heart rate was investigated in a longitudinal twin study, based on two measurements between the ages of 9 and 14 years. ASB was defined as a broad continuum of externalizing behavior problems, assessed at each occasion through a composite measure based on parent ratings of trait aggression, delinquent behaviors, and psychopathic traits in their children. Parent ratings of ASB significantly decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 47 publications
(69 reference statements)
5
45
3
Order By: Relevance
“…1. Although some empirical support for the proposed model has been documented [38], one study found that the relationship between resting heart rate and antisocial behavior in children was almost entirely explained by genetic influences [3]. With the dearth of replicated studies, additional research on autonomic arousal can reveal whether findings that challenge the model exist and thus, shed light on this important issue raised in DLC criminology.…”
Section: Challenges To the Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…1. Although some empirical support for the proposed model has been documented [38], one study found that the relationship between resting heart rate and antisocial behavior in children was almost entirely explained by genetic influences [3]. With the dearth of replicated studies, additional research on autonomic arousal can reveal whether findings that challenge the model exist and thus, shed light on this important issue raised in DLC criminology.…”
Section: Challenges To the Theorymentioning
confidence: 99%
“…They constitute a valid method to determine arousal as physiological responses are universal, sensitive, and objective [89]. They have been used in prospective studies on criminal and antisocial outcomes [3,63,77,90,116,151]. Psychophysiology is particularly useful in studying biological influences as specific measures have been identified.…”
Section: Autonomic Arousalmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible mechanism is a reduced functioning of the right hemisphere of the brain (Baker et al 2009;Raine 2002a). The right hemisphere controls autonomic functions, such as respiration and heart rate.…”
Section: Resting Heart Ratementioning
confidence: 99%
“…The success of this specific high resolution approach is illustrated by the meta-analytic finding of robust but opposite COMT effects on brain activation in emotional and executive tasks obtained in functional neuroimaging studies (Mier et al 2010). Most of the less specific but reliable markers of impaired brain and autonomic function in violence such as reduced neural activity to targets (amplitudes of the P300 component), reduced skin conductance, and heart rate variability still remain to be examined for G 9 E. Initial findings suggest that the endophenotype approach may be important to dissect genetic pathways to aggression, as genetic influences on psychophysiological (cardiac) function appeared to mediate the effects on aggression in a longitudinal twin study (Baker et al 2009). …”
Section: Directions For Future Researchmentioning
confidence: 99%